Long-term prognosis of culotte versus different crush strategies in management of unprotected left main bifurcation coronary lesions: a meta-analysis - Mou, Huaming; Yin, Li; Zhu, Feng; Li, Shasha; Zhang, Jianming; Pang, Xiaohua; Yang, Jianjun; Yu, Shimei; Mou, Yangjun; Wang, Doudou; et al. (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the long-term clinical effects of Culotte and different Crush techniques in the treatment of unprotected left main bifurcation coronary lesions to determine the best percutaneous coronary intervention strategy. Method: The systematic review and meta-analysis comprised search on PubMed, Embase, Cochrane Library, WanFang Data and the China National Knowledge Infrastructure literature databases to locate randomised controlled trials and cohort studies published in Chinese and/or English language till June 2021 and comprised application of Culotte and Crush stenting techniques for percutaneous coronary intervention in patients with unprotected left main bifurcation coronary lesions. The selected studies were analysed for quality, publication bias and heterogeneity. Results: Of the 197 studies located, 8(4.06%) were subjected to meta-analysis. The incidence of major adverse cardiac events in the Mixed-Crush group was higher than the Culotte group (p=0.02), which, in turn, was higher than the Double Kiss Crush group (p<0.0001), The incidence of target lesion revascularisation in the Culotte group was significantly higher than Double Kiss Crush group (p<0.001). The incidence of myocardial infarction in the Culotte group was higher than the Double Kiss Crush group (p=0.04). The incidence of cardiogenic death in the Double Kiss Crush group was similar to that in the Culotte group (p=0.32). Conclusion: Patients in the Double Kiss Crush group had the most long-term benefits, while those receiving Mixed Crush had the least long-term benefits. Key Words: Culotte, Crush, Unprotected left main bifurcation coronary lesion, Meta-analysis, Systemic review.